PERAN STIMULASI ORANG TUA TERHADAP PERKEMBANGAN ANAK USIA DINI DI MASA PANDEMI COVID 19 DI DESA KADUAGUNG TENGAH KECAMATAN CIBADAK KABUPATEN LEBAK - Hani Sutianingsih; Rery Kurniawati; Nani Yuningsih; Darti Rumiatun (Jurnal Medikes (Media Informasi Kesehatan), 2021)
Based on data on pediatric patients less than 18 years old with confirmed COVID 19, it was 3.23% and 11.4% suspected cases of COVID 19 for children aged less than 18 years. This shows that childhood is a vulnerable period for contracting COVID 19. Childhood is an important period in human life, especially early childhood. This is because at an early age, children begin to be sensitive or sensitive to receive various kinds of stimuli from outside the child. Therefore, at an early age it is very important to provide appropriate stimulation or stimulation to children, so as to optimize aspects of child development. Proper stimulation will stimulate the child's brain so that the child's development can be optimal, especially during the COVID-19 pandemic which demands the implementation of social distancing. The study design was cross sectional with a total of 50 respondents. The subjects of this study were parents of early childhood (5-6 years). The statistical test used is Chi squared. Based on the results of statistical tests, it was found that there was a relationship between the role of parental stimulation on early childhood development (5-6 years) of knowledge and attitudes of the bride and groom about reproductive and sexual health (p <0.05). It is hoped that parents will play a more active role in stimulating children's development by dealing with types of games that can stimulate gross motor development